2023
DOI: 10.1177/09603271231171642
|View full text |Cite
|
Sign up to set email alerts
|

Tricin attenuates diabetic retinopathy by inhibiting oxidative stress and angiogenesis through regulating Sestrin2/Nrf2 signaling

Abstract: To explore the potential function of tricin in diabetic retinopathy (DR) and investigate whether Sestrin2 is closely involved in DR. A single intraperitoneal injection of streptozotocin-induced diabetes model in Sprague-Dawley rats and a high glucose-induced retinal epithelial cell model in ARPE-19 cells were established. The retinas were removed and examined by hematoxylin-eosin (HE) staining and dihydroethidium (DHE) staining. The proliferation ability and reactive oxygen species (ROS) level of ARPE-19 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Sestrin2 alleviates the development of sepsis by inhibiting ferroptosis of dendritic cells in sepsis (Li et al 2021 ). In addition, research has found that Tricin alleviates DR by regulating Sestrin2/Nrf2 signaling to inhibit oxidative stress and angiogenesis (Yang and Li 2023 ). In addition, Sestrin2 has important clinical functions in a variety of metabolic diseases, such as diabetes and its complications, which can reduce insulin resistance by regulating glucose and lipid homeostasis, and studies have shown that serum Sestrin2 levels are significantly reduced in obese children and diabetic nephropathy patients (Lee et al 2012 ; Mohany and Al Rugaie 2020 ; Nourbakhsh et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sestrin2 alleviates the development of sepsis by inhibiting ferroptosis of dendritic cells in sepsis (Li et al 2021 ). In addition, research has found that Tricin alleviates DR by regulating Sestrin2/Nrf2 signaling to inhibit oxidative stress and angiogenesis (Yang and Li 2023 ). In addition, Sestrin2 has important clinical functions in a variety of metabolic diseases, such as diabetes and its complications, which can reduce insulin resistance by regulating glucose and lipid homeostasis, and studies have shown that serum Sestrin2 levels are significantly reduced in obese children and diabetic nephropathy patients (Lee et al 2012 ; Mohany and Al Rugaie 2020 ; Nourbakhsh et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been systematically shown, in in vitro and in vivo studies, that exposure to a high level of glucose induces a decrease in Nrf2 levels, particularly in the nucleus, but also total Nrf2 in all types of retinal cells: RPE cells, mainly investigated in ARPE-19 cells [392][393][394], endothelial cells, mainly HREC cells [395], Müller cells [23,396], and ganglion cells [397]. In vivo experiments also showed that diabetes decreases Nrf2 retinal content even during the early periods of diabetes before vascular alterations occur [378,379,398,399]. As mentioned earlier, Nrf2 controls the gene transcription of several antioxidant signals, some of them crucial to glutathione (GSH) generation, such as glutathione peroxidase and the catalytic subunit (xCT) of the cystine/glutamate antiporter X c − system (see [23] for a review).…”
Section: Diabetic Retinamentioning
confidence: 98%
“…Tricin reduces ROS production in endothelial cells, leading to downregulation of vascular endothelial growth factor receptor 2 (VEGFR2) signaling and inhibition of HIF-1α accumulation in tumor cells, resulting in decreased expression of VEGF [ 71 ]. Yang et al discovered that tricin inhibit angiogenesis and oxidative stress in retinal epithelial cells of DR rats by reinforces the Sestrin2/Nrf2 signaling pathway [ 72 ].…”
Section: Antioxidant Therapeutic Strategiesmentioning
confidence: 99%
“…Due to its high capacity for oxygen uptake, the retina is particularly vulnerable to oxidative stress in diabetes. The diabetic environment promotes oxidative stress, and molecules or medicines with antioxidant properties could be suitable candidates for attenuating DR [ 72 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%